2002
DOI: 10.1023/a:1020966008615
|View full text |Cite
|
Sign up to set email alerts
|

The 78 kDa Glucose-Regulated Protein (GRP78/BIP) Is Expressed on the Cell Membrane, Is Released into Cell Culture Medium and Is Also Present in Human Peripheral Circulation

Abstract: In human rabdomiosarcoma cells (TE671/RD) chronic exposure to 500 nM thapsigargin (a powerful inhibitor of the endoplasmic reticulum Ca2+-ATPases) resulted in the induction of the stress protein GRP78/BIP. Making use of the surface biotinylation method, followed by the isolation of the GRP78 using ATP-agarose affinity chromatography, it was found that a fraction of the thapsigargin-induced GRP78 is expressed on the cell surface. The presence of GRP78 on the membrane of thapsigargin-treated cells was confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 28 publications
8
75
0
Order By: Relevance
“…We demonstrate that during in vitro differentiation there is an increase in the expression levels of GRP-78 in primary calvarial cells. This observation corroborates well with the published report showing expression of GRP-78 on the plasma membrane as well as in the culture medium of rabdomiosarcoma cells (1). Recently, GRP-78 has also been reported to be present in the secretome of mesenchymal stem cells, and the expression levels increased upon induction of in vitro differentiation for 48 h (12).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We demonstrate that during in vitro differentiation there is an increase in the expression levels of GRP-78 in primary calvarial cells. This observation corroborates well with the published report showing expression of GRP-78 on the plasma membrane as well as in the culture medium of rabdomiosarcoma cells (1). Recently, GRP-78 has also been reported to be present in the secretome of mesenchymal stem cells, and the expression levels increased upon induction of in vitro differentiation for 48 h (12).…”
Section: Discussionsupporting
confidence: 93%
“…It plays a critical role in viral entry of Coxsackie B and Dengue viruses (6 -9). Recent studies have demonstrated GRP-78 as a secretory protein (1,12), indicating a possible extracellular function for GRP-78. One study points to an extracellular role of GRP-78 in the zona pellucida regulating the penetration of sperm by modulating calcium ions (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas BiP is generally thought to play a role in the structural maturation of nascent proteins in the ER, recent observations have shown that it may also have functions at the cell surface (23,27,28). BiP has been shown to associate with major histocompatibility complex class I protein (MHC class I) at the cell surface (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies demonstrate that GRP78 is also located on the cell surface. Cell surface expression of GRP78 was first detected in thapsigargin-treated human rhabdomyosarcoma cells [18,19]. Second, GRP78 was found to associate with MHC class I molecules on the cell surface.…”
Section: Grp78 Protein and Expressionmentioning
confidence: 98%